Partial epilepsies: a brief overview - Cendes,Fernando (2006)
INTRODUCTION: The epilepsies represent a heterogeneous group of disorders with diverse etiologic, electrographical and behavioral seizure patterns. OBJECTIVES: To review recent concepts about epileptogenesis and seizure-induced damage in partial epilepsies. METHODS: Critical review and discussion of some of the relevant papers in this topic. RESULTS: Mechanisms that are responsible for, or influence, the development of an epileptic condition, as well as its progression, are quite complex, and data on literature are sometimes apparently contradictory. CONCLUSION: This brief overview serves as an introductory remark to the review papers in this supplement.